Eradication of poliomyelitis in countries affected by conflict - R.H. Tangermann; H.F. Hull; H. Jafari; B. Nkowane; H. Everts; R.B. Aylward (The World Health Organization, 2000)
The global initiative to eradicate poliomyelitis is focusing on a small number of countries in Africa (Angola, Democratic Republic of the Congo, Liberia, Sierra Leone, Somalia, Sudan) and Asia (Afghanistan, Tajikistan), where progress has been hindered by armed conflict. In these countries the disintegration of health systems and difficulties of access are major obstacles to the immunization and surveillance strategies necessary for polio eradication. In such circumstances, eradication requires special endeavours, such as the negotiation of ceasefires and truces and the winning of increased direct involvement by communities. Transmission of poliovirus was interrupted during conflicts in Cambodia, Colombia, El Salvador, Peru, the Philippines, and Sri Lanka. Efforts to achieve eradication in areas of conflict have led to extra health benefits: equity in access to immunization, brought about because every child has to be reached; the revitalization and strengthening of routine immunization services through additional externally provided resources; and the establishment of disease surveillance systems. The goal of polio eradication by the end of 2000 remains attainable if supplementary immunization and surveillance can be accelerated in countries affected by conflict.